2004
DOI: 10.1023/b:joir.0000025133.54118.1e
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Potential Predation Costs of Male Decoration and Courtship Display in Wolf Spiders Using Video Digitization and Playback

Abstract: We used video digitization and playback techniques to examine the potential predation risk of leg decorations and visual displays of male wolf spiders

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 49 publications
(66 reference statements)
3
30
1
Order By: Relevance
“…In general, sexual dimorphism is the product of sexual selection (Andersson 1994), and it often takes the form of exaggerated male traits, armaments, or ornaments that confer reproductive advantages through either increased mate attraction or successful intrasexual competition for mates or preferred breeding habitat (Shuster and Wade 2003). Such traits are costly for the male to possess (Kotiaho 2001), as they can increase predation risk (Koga et al 2001;Pruden and Uetz 2004), energetic costs (Evans and Thomas 1992;Allen and Levinton 2007), or foraging costs (Evans and Thomas 1992). The cost of possessing an exaggerated morphological trait moderates the degree of exaggeration of the trait.…”
Section: Introductionmentioning
confidence: 99%
“…In general, sexual dimorphism is the product of sexual selection (Andersson 1994), and it often takes the form of exaggerated male traits, armaments, or ornaments that confer reproductive advantages through either increased mate attraction or successful intrasexual competition for mates or preferred breeding habitat (Shuster and Wade 2003). Such traits are costly for the male to possess (Kotiaho 2001), as they can increase predation risk (Koga et al 2001;Pruden and Uetz 2004), energetic costs (Evans and Thomas 1992;Allen and Levinton 2007), or foraging costs (Evans and Thomas 1992). The cost of possessing an exaggerated morphological trait moderates the degree of exaggeration of the trait.…”
Section: Introductionmentioning
confidence: 99%
“…predators for which signals reveal the presence of potential prey; Haynes & Yeargan, 1999;Rosenthal, 2007;Zuk & Kolluru, 1998). Courtship display of male S. ocreata is conspicuous and clearly detectable by predators (Pruden & Uetz, 2004;Roberts et al, 2007;Roberts & Uetz, 2008), and males have been shown to cease courting in the presence of predator cues (Fowler-Finn & Hebets, 2011;Lohrey, Clark, Gordon, & Uetz, 2009). In this context, that is, courting when behaviour of others indicates female presence nearby, eavesdropping might be seen as tipping the balance of the trade-off between mating success versus mate competition and predation risk.…”
Section: Discussionmentioning
confidence: 99%
“…This variaCompensation for injury in wolf spider courtship tion suggests that males are tactically tailoring their courtship activity to match the costs and benefits of performance. A more active, conspicuous, performance might increase the probability of mating but might also carry costs of energy use and exposure to diurnal predators that are abundant in the area where we collected spiders (e.g., birds, wasps, toads, other spiders) (wise & chen 1999a, 1999bpruDen & uetz 2004). Such interpretation would suggest that young virgin females are at a premium and worth the additional performance costs, especially if life expectancy is diminished by previous loss of forelegs.…”
Section: Discussionmentioning
confidence: 99%